Participation and commitment of community actors and state entities in the management of the archaeological zone of the Necropolis of Ancón, district of Ancón, Lima-Peru (2018-2020) - Chavarría Ramírez, Carmen Beatriz (2023)
Between 2017-2020, the Ministry of Culture implemented for the first time a mechanism for citizen participation in Ancon to bring together institutional actors and community actors in the district in a space for dialogue and develop activities collaboratively in favor of the archaeological site Necro-polis de Ancón, district of Ancón, Lima-Peru. This article addresses the scope and limitations of this experience of citizen participation for the social appropriation and sustainability of the Necropolis of Ancón, as well as the motivation and commitment of the participating multilevel actors through a participant research methodology that uses documentary review and interviews. The article reaffirms the need for citizen participation to recover archaeological sites through public management that involves the population not only as beneficiaries of the social use, but also promotes their leading role in decision-making.